Na+ diffusion mechanism and transition metal substitution in tunnel-type manganese-based oxides for Na-ion rechargeable batteries. Issue 2 (1st December 2021) - Quinzeni, Irene; Fujii, Kotaro; Bini, Marcella; Yashima, Masatomo; Tealdi, Cristina
Abstract : Structural, computational and electrochemical investigations are combined to study the intercalation properties of tunnel-type Na0.44 MnO2 and Cu-substituted Na0.44 MnO2 . Abstract : Na0.44 MnO2 (NMO) with a tunnel-type structure is a reference cathode material for rechargeable Na-ion batteries. In this work, structural, electrochemical and computational investigations are combined to study the properties of this material, particularly with reference to Cu substitution in the structure. For the first time, molecular dynamics (MD) is used to obtain insights into the mechanisms of Na + diffusion in NMO, highlighting the role of structural modifications and Na distribution. The main results allow the investigation of the implication of high temperature treatments and the effect of Cu substitution on the defect and transport properties of the material with a tunnel-type structure. From an experimental point of view, the substitution promotes an increased stability of the material upon cycling and an improved capacity particularly at higher discharging rates, that stems from the synergistic effects of the composition, morphology and multiple polymorphs of the sample.